Electrochemical sensing of hydrogen peroxide using Pd@Ag bimetallic nanoparticles decorated functionalized reduced graphene oxide. (10th February 2018) - Guler, Muhammet; Turkoglu, Vedat; Bulut, Ahmet; Zahmakiran, Mehmet
Abstract: In this study, an excellent sensitive, selective, and stable electrochemical sensor was fabricated for the determination of hydrogen peroxide (H2 O2 ) using nafion (Nf) and Pd@Ag bimetallic nanoparticles supported on (3-aminopropyl)triethoxysilane (APTES) functionalized reduced graphene oxide (rGO-NH2 ) modified glassy carbon (GC) electrode. The synthesized nanocomposites were characterized using Fourier transform infrared spectroscopy (FTIR), X-ray powder diffractometer (XRD), and High-resolution transmission electron microscopy (HRTEM). The electrochemical properties of the nanocomposites were investigated by means of electrochemical impedance spectroscopy (EIS) and cyclic voltammetry (CV). Under optimized conditions, the electrochemical detection of H2 O2 was carried out using amperometric method as well as CV. The linear range for H2 O2 determination was 0.002–19.500 mM with a detection limit of 0.7 μA and sensitivity of 1307.46 μA mM −1 cm −2 due to the strong synergistic effect between Pd and Ag nanoparticles. The fabricated sensor was used for the determination of H2 O2 in milk samples. The obtained results showed that the novel Nf/Pd@Ag/rGO-NH2 /GC sensor can be used for the determination of H2 O2 in real samples. Graphical abstract: